Properties And Characterisation Of Bamboo Cellulose Nanofibre Reinforced Polylactic Acid – Chitosan Nanocomposites - Gideon, Olaiya Niyi (2022)
Potential polymeric materials' mechanical and degradation properties are significant for green manufacturing. PLA has been reported to be an adaptable biopolymer to replace primary synthetic polymer in industrial applications. However, PLA has poor tensile strength and toughness because of its brittleness. In this study, chitosan and cellulose nanofibre (CNF) was incorporated in PLA to enhance its properties for potential green plastic industrial material applications.